Determination of Talniflumate and Niflumic Acid in Human Plasma by Liquid Chromatography-Tandem Mass Spectrometry - KANG, Wonku; KIM, Kibum (Analytical Sciences, 2009)
A simple and rapid quantification method was developed for determining both talniflumate and niflumic acid in human plasma. After simple protein precipitation with acetonitrile, the analytes were chromatographed on a reversed-phase C18 column and detected by LC/MS/MS with electrospray ionization. The assay accuracy and precision were within the FDA guidance for the analytical method validation. This method was used to measure the plasma concentrations of both compounds from healthy subjects after a single oral dose of talniflumate, 740 mg.